Chapter 8: research agenda - Yildirim, Alp; Reefke, Hendrik; Aktas, Emel (Springer, 2023)
This book illustrates the applications of mobile robot systems in warehouse operations with an integrated decision framework for their selection and application. Mobile robot systems are an automation solution in warehouses that make order fulfillment agile, flexible and scalable to cope with the increasing volume and complexity of customer orders. Compared with manual operations, they combine higher productivity and throughput with lower operating costs. As the practical use of mobile robot systems is increasing, decision-makers are confronted with a plethora of decisions. Still, research is lagging in providing the needed academic insights and managerial guidance. The lack of a structured decision framework tailored for mobile robot system applications in warehouses increases the probability of problems when choosing automation systems. This book demonstrates the characteristics of mobile robot systems which reinforce warehouse managers in identifying, evaluating and choosing candidate systems through multiple criteria. Furthermore, the managerial decision framework covering decisions at strategic, tactical and operational levels in detail helps decision-makers to implement a mobile robot solution step-by-step. This book puts special emphasis on change management and operational control of mobile robots using path planning and task allocation algorithms. The book also introduces focus areas that require particular attention to aid the efficiency and practical application of these systems, such as facility layout planning, robot fleet sizing, and human-robot interaction. It will be essential reading for academics and students working on digital warehousing and logistics, as well as practitioners in warehouses looking to make informed decisions.
Keywords: retail; warehouse operations; Amazon; automation solutions; mobile robot systems; change management